2014
DOI: 10.1186/1475-2875-13-404
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of 16 severe Plasmodium vivax cases from three municipalities of Colombia between 2009 and 2013

Abstract: BackgroundPlasmodium vivax, the most geographically distributed cause of malaria, accounts for more than 70% of cases in the Americas. In Colombia, P. vivax was responsible for 67.3% of cases in the last five years. Despite vivax malaria impact worldwide, historically it has been neglected and considered to be a benign disease. In the last decade medical literature reports have emerged countering this benign outlook. This study pretends to describe the clinical and paraclinical profile of severe vivax malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
4
17
1
1
Order By: Relevance
“…Similarly in the study conducted by Dilip R Patil et al (14) incidence of fever with chills and rigors is 98%. Similar findings was observed in a study done by Apte et al (18) and Echeverri et al (19) , O'brien et al (16) . In the present study, examination findings showed, pallor, Icterus, Pedal edema, Hepatomegaly, and Splenomegaly amongst study population was present in 13.33%, 21.33%, 8%, 5.3% and 77.33 %, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly in the study conducted by Dilip R Patil et al (14) incidence of fever with chills and rigors is 98%. Similar findings was observed in a study done by Apte et al (18) and Echeverri et al (19) , O'brien et al (16) . In the present study, examination findings showed, pallor, Icterus, Pedal edema, Hepatomegaly, and Splenomegaly amongst study population was present in 13.33%, 21.33%, 8%, 5.3% and 77.33 %, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…This is in accordance to study conducted by Dilip R Patil et al, (14) in which also higher incidence of vivax malaria was seen in the age group of 21 to 30 (23.53%). 23.15%, Similar findings was observed in the study conducted by Nadkar et al, (15) , O'brien et al, (16) and Bansal et al. (17) in which 21 to 30 years was observed in 23.15%, 37.5%, and 25.9% respectively .…”
Section: Discussionsupporting
confidence: 80%
“…In this tropical epidemiological scenario, clinical studies addressing that topic would also be useful, given that few studies in the country have assessed the epidemiology of severe P. vivax malaria [11,32], which has been largely documented and reported in other countries of Latin America, such as Venezuela [33][34][35] and Brazil [36][37][38], as well in Asia [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Although P. vivax infection is usually nonfatal, severe complications, including renal failure, severe anemia, and cerebral malaria, have been reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Because infections with P. vivax parasites can recrudesce months or years after the initial infection, the parasites are also more difficult to eliminate from the community.…”
mentioning
confidence: 99%